Adhesion conditions simulation of an experimental vehicle - Jilek, Petr; Šefčík, Ivo (Univerzita obrany v Brně, 2017)
The contribution deals with the possibility of adhesion forces change between a wheel of a road vehicle and a road. As a system for adhesion forces change is used an alternative to commercially available device SkidCar. Then the measured courses are compared to unique device assembled at Department of Transport Means and Diagnostics. This device is named SlideWheel. The adhesion characteristics change is implemented in form of radial reaction decrease of an automobile wheel. The intensity of radial reaction change is driven by help of auxiliary additional wheels.
Simulace adhezních podmínek na experimentálním vozidle
Keywords: automobile; skid; adhesion; automobil; smyk; adheze